The Principle of Self-Submission in Sharia Economic Dispute Resolution: A Critical Examination through Friedman’s Legal System Theory - Asyiqin, Istianah Zainal; Akbar, M. Fabian; Onielda, Muhammad Daffa Auliarizky (Universitas Negeri Gorontalo, 2025)
The principle of self-submission refers to the voluntary acceptance of a specific legal framework, particularly within Sharia economic dispute resolution. Law No. 3 of 2006 expanded the jurisdiction of Indonesia’s Religious Courts to adjudicate Sharia economic disputes, allowing non-Muslim litigants to participate under the condition of self-submission. While this legal provision promotes inclusivity, its practical application remains underexplored, particularly concerning its consistency with fundamental legal principles and its effectiveness in ensuring legal certainty. This study addresses this gap by critically examining the normative foundations and implementation of self-submission in Sharia economic dispute resolution through the lens of Lawrence M. Friedman’s legal system theory, which evaluates legal substance, legal structure, and legal culture. Employing a normative juridical approach, this research analyses statutory regulations, legal precedents, and court decisions to assess self-submission's coherence, adaptability, and limitations in Sharia economic adjudication. The findings indicate that while the principle of self-submission is structurally embedded within the legal system, its enforcement faces challenges in judicial interpretation, procedural inconsistencies, and the extent of its applicability to non-Muslim litigants. Furthermore, the study identifies gaps in legal certainty and harmonization with broader national and international legal frameworks. As a contribution to the discourse on Sharia economic law, this research proposes normative refinements and procedural enhancements to improve the clarity and effectiveness of self-submission, thereby strengthening Indonesia’s Sharia economic dispute resolution mechanism. These findings have broader implications for legal pluralism and the evolution of Sharia economic law in multi-religious societies.